2023
DOI: 10.1002/jmv.28898
|View full text |Cite
|
Sign up to set email alerts
|

Association between vaginal microbiota and the progression of ovarian cancer

Abstract: Ovarian cancers, especially high-grade serous ovarian cancer (HGSOC), are one of the most lethal age-independent gynecologic malignancies. Although pathogenic microorganisms have been demonstrated to participate in the pathogenesis of multiple types of tumors, their potential roles in the development of ovarian cancer remain unclear. To gain an insight into the microbiome-associated pathogenesis of ovarian cancer and identify potential diagnostic biomarkers, we applied different techniques to analyse the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Another study identified the presence of Brucella , Chlamydia , and Mycoplasma in ovarian cancer tumor cells, with Brucella believed to drive pelvic inflammation, leading to ovarian cancer [ 38 , 79 ]. Chlamydia significantly increases the risk of ovarian cancer, although further research is needed to elucidate Mycoplasma ’s role [ 41 ].…”
Section: Microbiome and The Diagnosis And Treatment Of Ovarian Cancermentioning
confidence: 99%
“…Another study identified the presence of Brucella , Chlamydia , and Mycoplasma in ovarian cancer tumor cells, with Brucella believed to drive pelvic inflammation, leading to ovarian cancer [ 38 , 79 ]. Chlamydia significantly increases the risk of ovarian cancer, although further research is needed to elucidate Mycoplasma ’s role [ 41 ].…”
Section: Microbiome and The Diagnosis And Treatment Of Ovarian Cancermentioning
confidence: 99%
“…While some evidence from the literature has been reported, the available data are not consistent. In the context of OC, this potential relationship is even more debated, as OC etiology can be attributed to multifactorial agents, including genetic predisposition, family history, and hormonal status [16,17].…”
Section: Introductionmentioning
confidence: 99%